Small ligand–globin interactions: Reviewing lessons derived from computer simulation - Capece, Luciana; Boechi, Leonardo; Perissinotti, Laura L.; Arroyo-Mañez, Pau; Bikiel, Damián E.; Smulevich, Giulietta; Marti, Marcelo A.; Estrin, Dario A. (Biochimica et biophysica acta, 2013)
In this work we review the application of classical and quantum-mechanical atomistic computer simulation tools to the investigation of small ligand interaction with globins. In the first part, studies of ligand migration, with its connection to kinetic association rate constants (kon), are presented. In the second part, we review studies for a variety of ligands such as O2, NO, CO, HS−, F−, and NO2− showing how the heme structure, proximal effects, and the interactions with the distal amino acids can modulate proteinligand binding. The review presents mainly results derived from our previous works on the subject, in the context of other theoretical and experimental studies performed by others. The variety and extent of the presented data yield a clear example of how computer simulation tools have, in the last decade, contributed to our deeper understanding of small ligand interactions with globins. This article is part of a Special Issue entitled: Oxygen Binding and Sensing Proteins. •We review the use of simulation tools to study ligand interactions with globins.•We describe ligand migration, entry and exit to/from the active site.•We describe, for different ligands, how the metalligand bond can be modulated.